Sumoylation as an Emerging Target in Therapeutics against Cancer - Liu, Sitong; Wang, Lichun; Jiang, Dongjun; Wei, Wei; Nasir, Mushyeda F.; Khan, Muhammad Saad; Yousafi, Qudsia; Liu, Xintong; Fu, Xueqi; Li, Xiaomeng; Li, Jiang (Current Pharmaceutical Design, 2020)
Sumoylation is the Post-translational modification gaining most of the research interest recently. Sumoylation is involved in various crucial functions of the cell such as regulation of cell cycle, DNA damage repair, apoptosis, etc. Oncology is advancing in radiotherapy, targeted chemotherapy, various forms of immunotherapy and targeted gene therapy. Researches are being conducted to prove its connotation with a variety of cancers and inhibitors are being developed to obstruct the fatal effect caused by misbalance of the SUMO-catalytic cycle. It has been shown that up-regulation of certain enzymes of Sumoylation correlates with cancer incidence in most of the cases. However, in some cases, down-regulation also associates with cancer invasion such as underexpression of UBC9 in initial stage breast cancer. This can aid in future study, treatment, and diagnosis of a variety of cancers including breast cancer, prostate cancer, lung adenocarcinoma, melanoma, multiple myeloma, etc. Various mechanistic assays are being developed and used to identify potential inhibitors against the dysregulated proteins of Sumoylation. This review summarizes the normal roles of the enzymes involved in the SUMOcatalytic cycle, their misbalanced regulation leading to tumorigenesis and nearly all the potent inhibitors identified to date, while after detailed studied it was observed that ML-792 could be a promising inhibitor in treating cancers by inhibiting Sumoylation enzymes.
Keywords: Post-translational modifications